POLITIK HUKUM PERKAWINAN DAN PERKAWINAN BEDA AGAMA DI INDONESIA - Sri Wahyuni (LP3M IAI Al-Qolam Malang, 2014)
This article discusses about the politics of Indonesia marriage law, especially relates to the law of interreligious marriage. Interreligious marriage always becomes a polemic. There is an argument says that it’s forbidden but there is another which says that there is a vacuum of law in the interreligious marriage, because it’s not regulated clearly. Furthermore, by observing to the politic of the Marriage law legislation, the legislator tended to prohibit the interreligious marriage, especially the Muslim community who regarded that the interreligious marriage is incompatible to the Islamic law. Keywords: marriage law, interreligious marriage, marriage law legislation